The influence of smoking cessation, regular physical exercise and/or physical activity on survival: a 13 years cohort study of the Indonesian population in Jakarta (Medical Journal of Indonesia, 2002)
Preventing atherosclerosis with smoking cessation, regular physical exercise and/or physical activity known as SOK (S-top/ no S-moking, sp-O-rt/ physical exercise, wor-K/ physical activity) is a simple preventive measure, which can be applied in the community. To determine the role of SOK on survival, to create cardiovascular risk score for Indonesian patients and to have a special formula to predict survival. A historical cohort study over thirteen years recruited from the subpopulation MONICA patients who resided at three districts of South Jakarta. Patients were divided into two groups, those with SOK and those without (non-SOK group). Assessment included complete history including cardiovascular risk factors (hypertension, diabetic, hyperlipidemia, obesity), physical examination, laboratory examination, twelve-lead ECG recording and level of physical activity/exercise. Outcomes included survival rate and all-cause of mortality. Statistical analysis included kappa statistic and various survival analyses. 479 participants were included in the SOK study. Mean age 46 years (range 25-64), 56% female. Cardiovascular mortality rate (including stroke) was 1.2% per year and 42.9% of mortality caused by heart disease. Survival rate was higher in SOK group compared with non-SOK (95.7% vs 81.1%) with Hazard Ratio (HR) 0.2 for SOK group (95% CI 0.08-0.57, p=0.002) In relation to the cardiovascular mortality rate: 1) any physical activity/exercise (OK) vs no-OK will lower the risk; low-OK (HR 0.4, p=0.003), medium-OK (HR 0.32, p=0.004), high-OK (HR 0.000, p=0.000) 2) Smoking will increase the risk vs non-smoking (HR 4.99, p=0,000). For predicting the cardiovascular events in ten-year time (CV10), we formulated the Jakarta Cardiovascular Score. The score was divided into low-risk (-7-1) with CV10 <10%, average-risk (2-4) with CV10 = 10-20%, high-risk (score > 5) with CV10 >20%. Smoking cessation, regular physical exercise and/or physical activity is an effective method to reduce cardiovascular death, thus enhances the survival. We formulated a simple method to predict cardiovascular events in our community known as the Jakarta Cardiovascular Score. (Med J Indones 2002; 11: 230-41)Keywords: smoking, physical activity, survival, Jakarta cardiovascular score.